Short‐term upwelling events at the western African coast related to synoptic atmospheric structures as derived from satellite observations. Issue 1 (21st January 2014) - Desbiolles, F.; Blanke, B.; Bentamy, A.
<x xml:space="preserve">Abstract</x> [1] Satellite scatterometers provide continuously valuable surface wind speed and direction estimates over the global ocean on a regular grid both in space and time. The Level 3 data derived from the Advanced Scatterometer (ASCAT), available at 1/4° spatial resolution (hereafter AS25), and Quick Scatterometer (QuikSCAT), available on 1/2° and 1/4° horizontal grids (QS50 and QS25, respectively), are studied at regional scales in both the Benguela and Canary upwelling systems. They are compared to the European Center for Medium‐Range Weather Forecast surface wind analysis, with insight into their intrinsic and actual spatial resolutions. In the coastal band, the finest spatial patterns are found in the QS25 winds and are O(75 km). This demonstrates the sensitivity of the high‐resolution satellite‐derived winds to coastal processes related to sea surface temperature (SST) perturbations and land‐sea transition. Next, short‐lived upwelling episodes (SUEs) calculated from SST anomalies are defined consistently with the QS25 actual resolution. These cold events refer to local, short‐lived perturbations that add to seasonal upwelling variability. We characterize concomitant atmospheric synoptic conditions for SUEs identified at chosen latitudes and highlight two subregions in both upwelling systems, with contrasted patterns for the alongshore wind stress component and curl. The complexity of the latter patterns is closely linked to local, short‐term SST variability. Closer to the shore, numerical sensitivity experiments show that the imbalance between Ekman transport and Ekman pumping has an impact on ocean dynamics: wind reduction in the coastal QS25 forcing, partially induced by orography, tends to reduce coastal SST cooling.